Dinâmica da água e carboidratos durante período de repouso hibernal em pereira e pessegueiro nas condições de inverno ameno - Rickes, Letícia Neutzling (2012)
The translocation of water and carbohydrates in plant tissues temperate fruit still creates doubts in the scientific field and knows that it is a factor to overcome dormancy, because to be budburst is needed imports of soluble sugars, the which are derived from starch conversion adjacent tissues. This work aimed to evaluate biweekly water content (WC), content of total soluble sugars (TSS), sucrose content and starch during the winter period (June to September) in tissues of pear cvs. Housui and Packham's and peach cvs. Eldorado and Jubileu of the orchards belonging to the Agricultural Center of Palma UFPel. During data collection, four branches were collected from each cultivar were divided into three positions (basal, median, apical) to assess where the WC, they were divided in two tissues: bark and wood. It was found in pear cultivars in both tissue and skin tissue in the wood, do not show large differences in the dynamics of WC in the three positions studied during the winter period. However, peach WC on the wood was examined in more than one shell in the three positions of the branch. The observed increase in WC can be a physiological marker to break dormancy. This different behavior can be attributed to the accumulation of cold. Regarding the dynamics of carbohydrate species in the study behaved differently. In peach there was a significant increase in carbohydrate content in the apical position around the time of shooting, not unlike what was observed in the case of the pear. The lack of cold and thermal fluctuations directly affect the activity of hydrolytic enzymes, which explains the lack of starch degradation in the tissues of the pear. The two species have different requirements in relation to the accumulation of cold, explaining the different behavior in the dynamics of water and carbohydrates in the winter rest period.